METHODS OF PREVENTION OF CRIME, WHICH DETERMINE THE SOCIAL RELATIONSHIP OF IMPLEMENTATION OF THE PRINCIPLE OF INEVITABILITY OF LEGAL LIABILITY - Ахмедов, Вусал Алігісмат огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: to reveal a complex of socio-economic and legal measures to prevent and counteract crimes that encroach on the implementation of the principle of binding judgments. Methods of research: the methodological basis of the study consisted of general scientific methods of cognition, through which revealed the most effective ways to improve the efficiency of judicial decisions. Results: the author identifies a set of measures and methods for combating and preventing non-enforcement of court decisions in their totality and interconnection. Discussion: the author proposes to create appropriate conditions for prevention of investigated crimes at the legislative level. Discuss the thesis that the moment of committing such an offense, as failure to comply with a court decision, should be fixed in the criminal law, without regard to the procedure of enforcement proceedings. Execution of a court decision is an integral part of the right of everyone to judicial protection and covers, in particular, a legally determined set of actions aimed at protecting and restoring violated rights, freedoms, legal interests of individuals and entities, society, and the state. Failure to comply with the court ruling eliminates all activities of law enforcement agencies, the court, harms human rights and freedoms, violates the existing law and order, and such violations make it possible to trace the link between the rule of law and the principle of legal certainty in ensuring the binding nature of the court’s decision. In order to prevent the crimes investigated it is expedient to eliminate criminal gaps in the legal regulation of the terms of execution of court decisions. Legislative (in procedural codes) it is necessary to fix the terms of execution of court decisions depending on typical characteristics of their content. At the same time, such terms should not be connected with the terms of enforcement of enforcement proceedings. And this fully corresponds to the constitutional principle of binding judgments: a court decision which has become legally enforceable is enforceable by a person entrusted with a certain legal obligation, on a mandatory basis, on his or her own initiative. The involvement of public service providers in this process is the right, and not the obligation of the payer, and the absence of enforcement proceedings, in any case, does not allow for non-enforcement of a judicial decision. Making the appropriate changes to the procedural laws, fixing the exact terms of execution in the text of the court decision, will undoubtedly discipline the parties in the case, and will allow the effective implementation of the principle of individuality of legal liability. Among the priority directions of the reform of the state executive service, the researchers distinguish: the introduction of private executives, the creation of an appropriate self-government body, as well as effective monitoring mechanisms by the Ministry of Justice; formation of transparent incentives and publicity of the whole system of management of the efficiency of the executive service; creation of integrated information systems at the stage of execution of court decisions and collection of debts, including web-based modules for maintenance of electronic business and automated system of money restraint; raising awareness and communication with the community, the professional community and the general public on the reform of the executive service; raising the prestige of the profession, attracting and educating more qualified personnel. The introduction of an institution of private performers will be an important reform, as competition should reduce corruption in this area and increase the efficiency of enforcement of court decisions.